Characterization of coaptation gap in patients receiving tricuspid transcatheter edge-to-edge repair: initial observations from the bRIGHT TriClip study. (4th February 2022) - Donal, E; Sitges, M; Panis, V; Schueler, R; Lapp, H; Moellmann, H; Nickenig, G; Bekeredjian, R; Estevez, R; Atmowihardjo, I; Trusty, P; Lurz, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: As tricuspid transcatheter edge-to-edge repair (TEER) gains momentum, the proper measurement of coaptation gap to determine optimal patients for this therapy becomes increasingly important. Currently, a single septo-lateral measurement from the short-axis transgastric (SAX TG) or RV inflow/outflow biplane view is commonly used as the representative coaptation gap measurement for a patient. However, this measurement is not necessarily performed at the intended location for TEER and may overestimate the coaptation gaps to be treated. Purpose: To characterize the coaptation gap in patients receiving tricuspid TEER which may provide insights on how to best determine eligibility for edge-to-edge repair. Methods: bRIGHT is a prospective, multi-center, single arm post-market study evaluating the safety and effectiveness of the TriClip device in symptomatic patients with severe tricuspid regurgitation. Detailed echocardiographic coaptation gap measurements were performed on the first 46 subjects with available echo data by two experienced echocardiographers. Coaptation gap was measured at four levels in the SAX TG view (Figure 1) and also at the resulting long axis view from a orthogonal view taken from a RV inflow/outflow view obtained at the anterior, mid and posterior aspect of the tricuspid valve (Figure 2). Results: The biplane RV inflow/outflow and SAX TG views were available in 91% (42/46) and 93% (43/46) of subjects, respectively. From the SAX TG view, coaptation gap measured 9.0 ± 3.9 and 4.9 ± 2.7 mm in the central and mid regions of the anterior-septal coaptation line, and 7.6 ± 3.4 and 4.0 ± 2.1 mm in the central and mid regions of the septal-posterior coaptation line (Figure 1). The largest coaptation gap presented between the anterior and septal leaflets in 78% (33/43) of subjects, with the gap extending across the anterior-septal and septal-posterior coaptation lines in 98% (42/43) of subjects. Coaptation gap measured 6.2 ± 2.8, 6.6 ± 2.8 and 6.0 ± 3.5 mm in the anterior, mid and posterior aspects of the RV inflow/outflow view (Figure 2). In subjects with both views available, the SAX TG view resulted in larger coaptation gap measurements (+3.4 ± 3.0 mm) in 95% (38/40) of subjects. A significant, positive correlation was observed between the maximum biplane and transgastric measurements (rho = 0.648, p < 0.0001). Conclusion: A single septo-lateral measurement may overestimate the actual gap size and potentially exclude patients who are viable candidates for TEER. Measurements in both the SAX TG and RV inflow/outflow biplane should be taken into account when determining appropriateness of a given anatomy for tricuspid TEER Future work in larger cohorts is needed to determine which coaptation gap measurements are predictive of procedural outcomes and how these measurements may influence treatment strategy.